A STUDY ON SCREENING OF OSTEOSARCOMA U2OS CELL INHIBITING ACTIVE COMPONENTS FROM NIDUS VESPAE - Jiang, Zhenhuan; Jiang, Jiannong; Wang, Qiang; Zhang, Leiyan; Wu, Chenguang; Yang, Huilin (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This paper mainly examined the anti-osteosarcoma activity of total flavonoids extract from traditional Chinese medicine, nidus vespae. Orthogonal design was used to design the extraction process of total flavonoids. L(34) orthogonal test was performed and the extracts obtained by three optimal extraction processes were used for anti-tumour activity screening in order to determine the optimal anti-tumour effective component of nidus vespae. MTT assay was used to investigate the effect of nidus vespae extract on proliferation activity of osteosarcoma cells. Meanwhile, U2OS cell inhibitory capacities of extracts in three groups with higher total flavonoid contents were investigated and compared, and inhibition rates were calculated. The results showed that the optimal extraction process was ethanol concentration of 95%, 12-fold amount of ethanol relative to the weight of medicinal material, extraction times of 3 times, and extraction time of 2 hours. 9 extraction processes all showed proportional trend of cancer cell inhibition rate to extract concentration.